Direct Financial Compensation, The Result of A Study To Increase Motivation And Work Discipline Pt. Satyatama Graha Tara (Doli Siregar And Rekan Valuers & Property Consultants) Jakarta - Sukandi, Pipin; Mega Merah Jingga, Rembulan (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this research is to know the impact of direct financial compensation on the motivation and discipline of employees of a company. The study used a population analysis technique of 50 employees given questions and interviews. The data analysis techniques used are the classical assumption test, normality test, multicollinearity test, heteroskedasticity test, and F. test. The results of the data test explained that there was a positive and significant impact on the X1 variable (direct financial compensation) against variable Y (working discipline). Variable positive and significant impact X2 (work motivation) against variable Y (work discipline). Positive and significant impact on direct financial compensation variables (X1) and work motivation (X2) on working disciplines (Y) in α 0.05.